2017
DOI: 10.17957/tpmj/17.4003
|View full text |Cite
|
Sign up to set email alerts
|

Blood Donation; Knowledge, Attitude and Beliefs of the Female Attendants

Abstract: ABSTRACT:The participation of women in blood donation process has been scarce equally in low & high resourced countries. Every year 3.5 million blood donations are collected in Pakistan with very little percentage of females donating blood. Objective: The objective of the study was to assess the knowledge, attitude and beliefs of female attendants accompanying the patients. Study Design: Cross-sectional study. Setting: The Children's Hospital & Institute of Child Health, Lahore, regarding blood donation. Perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[11][12][13]15,[18][19][20][21][22][24][25][26]28,29,31,32,35,39 Two studies had 0% of HIV-reactive cases. [2][3][4][5][6][7][8][9][10][11] Another two studies had HIV frequency of 0.02% (N=26) and 0.07% (n= 20) of the screened population, all positive cases were men. 20,22 Irfan et al reported a low frequency (0.10%) of HIVpositive cases but faced difficulty in following up on reactive cases.…”
Section: Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13]15,[18][19][20][21][22][24][25][26]28,29,31,32,35,39 Two studies had 0% of HIV-reactive cases. [2][3][4][5][6][7][8][9][10][11] Another two studies had HIV frequency of 0.02% (N=26) and 0.07% (n= 20) of the screened population, all positive cases were men. 20,22 Irfan et al reported a low frequency (0.10%) of HIVpositive cases but faced difficulty in following up on reactive cases.…”
Section: Hivmentioning
confidence: 99%
“…1 An estimated 3.5 million blood donations are collected every year in Pakistan. 2 Blood transfusions are used mainly for chronically transfusion-dependent thalassemia patients, anemia due to poor health conditions, acute trauma, surgical procedures, hemorrhage and pregnancy-related complications. 5 An estimated one-fourth of the national annual blood collections are used for transfusion-dependent thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Females although representing half of our population but their participation in blood donation process has always been scarce in our country. 17 , 18 Moreover, Anti-A1 antibody testing was not performed. It can be considered as a pilot study and be further extended by performing Anti-A1 antibody testing in people of blood group of A2.…”
Section: Discussionmentioning
confidence: 99%
“…3 The number of voluntary donors is not up to the mark yet. 4 There are many barriers to the blood donation process like security of donors, lack of knowledge, counselling and education, misconceptions and myths related to blood donation, anxiety and different 1 Department of Hematology & Transfusion Medicine, 2 Department of Pediatric Hematology and Oncology, University of Child Health Sciences, The Children's Hospital, Lahore, Pakistan 3 Department of Hematology, FJMU, Lahore, Pakistan fears. These uncertainties reduce the rate of voluntary blood donations.…”
Section: Introductionmentioning
confidence: 99%